Safety and efficacy of sintilimab combined with oxaliplatin/capecitabine as first-line treatment in patients with locally advanced or metastatic gastric/gastroesophageal junction adenocarcinoma in a phase Ib clinical trial - Haiping Jiang; Yulong Zheng; Jiong Qian; Chenyu Mao; Xin Xu; Ning Li; Cheng Xiao; Huan Wang; Lisong Teng; Hui Zhou; Shuyan Wang; Donglei Zhu; et al. (BMC Cancer, 2020)
Abstract Background Sintilimab blocks the interaction between programmed death-1 (PD-1) and its ligands. The safety and efficacy of sintilimab combined with oxaliplatin/capecitabine (CapeOx) as first-line treatment were evaluated in patients with gastric (G)/gastroesophageal junction (GEJ) adenocarcinoma in a phase Ib clinical trial. Methods Patients with locally advanced or metastatic G/GEJ adenocarcinoma without previous systemic treatment were enrolled as one cohort of a multi-cohort study. Sintilimab was administered at a dose of 200 mg intravenously (IV) in combination with CapeOx (1000 mg/m2 capecitabine orally, bid, D1–14 and 130 mg/m2 oxaliplatin IV, D1) every 21 days for up to 6 cycles. After combination treatment, patients continued to receive sintilimab (200 mg) at 3 weekly intervals as maintenance therapy until progressive disease (PD), unacceptable toxicity, withdrawal of informed consent, or for up to 24 months. Adverse events (AEs) were monitored to assess safety in terms of their frequency, intensity and causality. The efficacy endpoints included the objective response rate (ORR), disease control rate (DCR), progression-free survival (PFS) and overall survival (OS). Tumor mutation burden (TMB) was evaluated for its association with clinical response. Results A total of 20 patients were enrolled and received sintilimab plus CapeOx. All patients reported treatment-related AEs (TRAEs). Grade 3–4 TRAEs were found in 11 (55.0%) patients. Seventeen patients obtained partial response and the ORR was 85.0% (95% CI: 62.1–96.8%). Three (15.0%) had stable disease and DCR was 100.0% (95% CI: 83.2–100.0%). As data cutoff of May 1, 2019, the median follow-up was 7.8 months. The median PFS was 7.5 months (95% CI: 6.2–9.4) and median OS had not been reached. The OS rates at 6 months and 12 months were 100.0 and 68.0%. No association was observed between TMB and efficacy. Conclusions Sintilimab combined with CapeOx as first-line treatment demonstrated acceptable safety and promising efficacy. Trial registration ClinicalTrials.gov, NCT02937116 . Registered 8 October 2016.